Strategy for development - Barratt, John; South African Institute of International Affairs (London : Macmillan [for the South African Institute of International Affairs], 1976)
This volume is based on papers presented at a conference in Johannesburg, December 4-7, 1974.
Includes bibliographies and index.
lje 14/12/18
Loans
Keywords: Economic development; Africa, Southern